Role of Visual Language in Marketing: Build and Implement Branding Identity on Mini-Market - Hamizar, Arizal; Masniati, Andi; Holle, Mohammad H; Mohamad, Syed Ismail Syed (Elite : English and Literature Journal, 2023)
This study aimed to gain a deeper understanding of the impact of visual language on building and sustaining a strong brand in the mini-market industry. Qualitative research has shown that visual language can have a powerful impact on consumer behavior and purchasing decisions. For example, the choice of colors, images, and symbols can evoke specific emotions and associations, influencing how consumers perceive and interact with the brand. This, in turn can impact brand loyalty, as consumers are more likely to return to brands that they perceive as being trustworthy and consistent. The use of visual language in branding is particularly important for mini markets, as these businesses compete in a crowded and highly competitive industry. By using visual language to create a strong brand image and establish brand associations, mini-markets can differentiate themselves from competitors, build a loyal customer base, and establish a strong reputation in the marketplace.